1D ANALYSIS OF LAND SUBSIDENCE IN SHANGHAI - J.-C. Chai; S.-L. Shen; H.-H. Zhu; X.-L. Zhang (International Association of Lowland Technology, 2005)
Land subsidence in Shanghai is investigated. The subsidence was mainly caused by excessive withdrawal of groundwater and since 1921, the measured subsidence was 2 to 3 m in the central area of the city. One-dimensional (1D) finite element consolidation analyses were conducted to simulate and predict the subsidence at Point-A, eastern part of Shanghai. The analysis result fairly simulated the field measured tendency and it indicates that the compression of the mucky clay layer, the silty clay layer in aquitard I and the third compression layer (aquitard II) contributes about 80% of the total subsidence. Also, it is shown numerically that for consolidation caused by groundwater level drawdown in an aquifer, the final state is a steady state water flow toward the aquifer, and the relative values of hydraulic conductivity of clayey layers above the aquifer have an important effect on calculated amount of settlement. Further, three possible scenarios were assumed for discussing the future subsidence. In the case of maintaining the groundwater level as it was in 2001, the predicted subsidence in 50 years is only about 2 mm. In the case of continuous drawdown of groundwater (1 m/year for aquifer IV and V, 0.5 m/year for aquifers II and III, and 0.2 m/year for aquifer I), in 50 years the predicted subsidence is about 1.25 m. If the groundwater level is recovered to zero elevation in all aquifers in the next 50 years, the predicted amount of heave is about 0.20 m.